(untitled) (Academicia Globe: Inderscience Research, 2022)
The article is focused on the problem of discrepancies LSG “educational process participants” in the Uzbek and English languages. It is dedicated to the lexical-semantic field of “education” and expressed with verbalizers that realize the field of “conceptual semantics of “educational process participants” compared in both languages. The distinctive features of constituents of analyzed LSG are illustrated with examples, supported with the opinions of scholars’ research work . The novelty of the article is the first comparative analysis of microfield “education” in the Uzbek and English languages